Rancang Bangun Aplikasi Penilaian Pembelajaran dalam Kelas PRODISTIK di MAN 1 Pasuruan Berbasis Android - Sya’bana, M. Ilham; Arief Tri Arsanto (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
The learning assessment process in the PRODISTIK MAN 1 Pasuruan class is carried out manually; therefore, it is less efficient and prone to errors. The purpose of this study is to develop an Android-based assessment application to make it easier for teachers and provide direct access to student scores. The method used is Waterfall, through the stages of needs analysis, design, implementation, and testing. Data were obtained through interviews and literature reviews. The application is equipped with login features, value input, and value access. Testing was carried out using black box and usability testing with 20 respondents. The results showed that all application functions run as expected with user satisfaction of 93.37%. This research is expected to contribute to the process of effective learning assessment.